Peran Serangga sebagai Vektor Penyakit Karat Puru pada Sengon (Albizia falcataria L. Fosberg) - Ananto Triyogo (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2012)
Sengon (Albizia falcataria L. Fosberg) forest plantations of community in Wonosobo District, Central Java wereattacked by gall rust disease. The objective of this research was to investigate the role of insects as a vector of gall rustdisease. The attack intensity was measured in the different ages of tree stand (1, 2, 3, 4, and 6 year old) with randomizedcomplete block design (RCBD) consisting of 3 blocks, 3 replications, and 3 sampling plots. The role of insect as a vectorwas tested using two different approaches: observation on the spores in the adult insect integument and artificial investationof insect containing spores on the healthy seedlings. The result of this research showed that the one year old of sengon hadhighest disease intensity (95.5%) and lowest disease incidence (56.96%). The identification showed that the insect belongsto Lepidoptera (Family Heliozelidae) completing the metamorphosis in the gall. Spores were found in the integument ofLepidoptera (Family Heliozelidae) at the average of 2.8 x 104 spore μL-1 insect-1. Artificial innoculation on healthy seedlingdid not show the infection symptoms by Uromycladium tepperianum until 5 weeks after innoculation.